Fusarium sp. Strain K-23 Alleviates Salt Stress in Arabidopsis thaliana Through its Root Hair Growth-Promoting Effect - Francis C. Onejeme; Adrián González Ortega-Villaizán; Estefanía Rodríguez-Dobreva; Basha Topel Prieto; Manish K. Patel; Selma Guendouzi; Priya Y. N. Reddy; Leonel E. Lopez; José M. Estevez; Karaba N. Nataraja; R. Uma Shaanker; Begoña Benito; et al. (Journal of Plant Growth Regulation, 2025)
Soil salinity is a significant abiotic stress factor that impedes plant growth and crop yield, particularly in arid and semi-arid regions. Recent reports indicate that 8.7% of soils globally and 20–50% of irrigated soils across all continents are affected by salt. This phenomenon jeopardizes the food security of more than 1.5 billion people worldwide. Numerous studies have elucidated the beneficial effects of diverse microbes on plant abiotic stress tolerance. In this study, we report on an observed molecular mechanism involved in the enhanced salt tolerance of Arabidopsis plants co-cultivated with the Fusarium sp. strain K-23. Employing a combination of transcriptomics, phenomics, reverse genetics, and live cell imaging, we elucidated the intricacies of biological processes that influence root growth in the interaction between A. thaliana and the fungus. Moreover, our research corroborated the beneficial effect of the fungus under salt-stress conditions for Arabidopsis and highlighted notable differences compared to previous studies. We utilized an RNA-seq approach to identify biological processes triggered in Arabidopsis roots that interact with K-23, resulting in increased salt tolerance. These experiments necessitated a more comprehensive investigation into the fungal influence on root hair development and elucidated that induced root hair growth was a prerequisite for the enhanced salt stress tolerance conferred by the fungus. Furthermore, we demonstrate that the fungus induces the expression of the NAC transcription factor JUNGBRUNNEN 1 ( JUB1 ). Elevated expression of JUB1 leads to repression of gibberellin biosynthesis, which, in turn, contributes to sustained root hair growth under salt stress conditions, which typically suppresses root hair growth substantially.

Identification of a drought stress response module in tomato plants commonly induced by fungal endophytes that confer increased drought tolerance - Adrián González Ortega-Villaizán; Eoghan King; Manish K. Patel; Estefanía Rodríguez-Dobreva; Marcia González-Teuber; Patricio Ramos; Jesús Vicente-Carbajosa; Begoña Benito; Stephan Pollmann (Plant Molecular Biology, 2025)
Global climate change exacerbates abiotic stresses, as drought, heat, and salt stresses are anticipated to increase significantly in the coming years. Plants coexist with a diverse range of microorganisms. Multiple inter-organismic relationships are known to confer benefits to plants, including growth promotion and enhanced tolerance to abiotic stresses. In this study, we investigated the mutualistic interactions between three fungal endophytes originally isolated from distinct arid environments and an agronomically relevant crop, Solanum lycopersicum . We demonstrated a significant increase in shoot biomass under drought conditions in co-cultivation with Penicillium chrysogenum isolated from Antarctica, Penicillium minioluteum isolated from the Atacama Desert, Chile, and Serendipita indica isolated from the Thar Desert, India. To elucidate plant gene modules commonly induced by the different endophytes that could explain the observed drought tolerance effect in tomato, a comprehensive transcriptomics analysis was conducted. This analysis led to the identification of a shared gene module in the fungus-infected tomato plants. Within this module, gene network analysis enabled us to identify genes related to abscisic acid (ABA) signaling, ABA transport, auxin signaling, ion homeostasis, proline biosynthesis, and jasmonic acid signaling, providing insights into the molecular basis of drought tolerance commonly mediated by fungal endophytes. Our findings highlight a conserved response in the mutualistic interactions between endophytic fungi isolated from unrelated environments and tomato roots, resulting in improved shoot biomass production under drought stress.

Distribution of indole-3-acetic acid in Petunia hybrida shoot tip cuttings and relationship between auxin transport, carbohydrate metabolism and adventitious root formation - Amir H. Ahkami; Michael Melzer; Mohammad R. Ghaffari; Stephan Pollmann; Majid Ghorbani Javid; Fahimeh Shahinnia; Mohammad R. Hajirezaei; Uwe Druege (Planta, 2013)

Subcellular localization and tissue specific expression of amidase 1 from Arabidopsis thaliana - Stephan Pollmann; Daniel Neu; Thomas Lehmann; Oliver Berkowitz; Tina Schäfer; Elmar W. Weiler (Planta, 2006)

Occurrence and formation of indole-3-acetamide in Arabidopsis thaliana - Stephan Pollmann; Axel Müller; Markus Piotrowski; Elmar Weiler (Planta, 2002)